The Influence of Learning Technology on Early Childhood Literacy Development in Indonesia - Maulinda, Rerin; Subhan, Roni; Yuliah, Yuliah; Abdullah, Dahlan (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. In the era of information and communication technology, the use of learning technology in Indonesia is increasingly widespread, including among young children. Today's children not only grow up in a technological environment, but also actively interact with digital devices from an early age. Early childhood literacy is key in understanding the influence of learning technology on their development. Purpose. The main aim of this research is to investigate to what extent and in what ways learning technology influences the literacy development of early childhood children in Indonesia. Through a quantitative approach and involving education students, this research seeks to provide a comprehensive picture of the positive and negative impacts of learning technology and identify factors that influence early childhood literacy. Method. The research employs a quantitative approach through a survey method, targeting 30 education students with a profound understanding of children's developmental stages. A questionnaire was crafted and disseminated through Google Forms to gather insights into students' perceptions and experiences related to the utilization of learning technology and its influence on the early childhood literacy development. The acquired data will undergo quantitative analysis techniques, emphasizing data reduction, presentation, and the derivation of conclusions. Results. The research results show that students have positive experiences in using learning technology, actively utilizing it, especially in the context of early childhood education. Positive perceptions also emerged regarding the influence of learning technology on literacy and motivation of young children. Its social and emotional impact is considered positive, contributing to the emotional well-being and social interactions of early childhood. Conclusion. The conclusion of this research is that learning technology has a positive role in enriching the experience of early childhood education in Indonesia. These positive impacts include increasing literacy, learning motivation, as well as social and emotional aspects of early childhood.